STATUS ANEMIA GIZI BESI DAN KONSUMSI ZAT GIZI PADA ANAK USIA SEKOLAH DI LIMA PANTI ASUHAN DI KOTA DENPASAR - Melisa dewi; Ketut Sutiari; lila Wulandari (ARCHIVE OF COMMUNITY HEALTH, 2012)
Iron de? ciency, anemia, cause a negative impact on health such as lowering levels of endurance,lowering concentration power of learning and child development disorders. This research aimsto identify iron de? ciency, anemia, status and nutrient intake in school age children at ? veorphanages in Denpasar.The design of this research was cross-sectional study conducted at ? ve orphanages in Denpasar.The 48 school age children were assigned using a systematic random sampling. Data of hemoglobin level were coollected using Cyanmethaemoglobin; nutrient intake and iron inhibitors using a SQFFQand questionnaire. Data wereanalyzed descriptivelyand presented in tablesand narrative.Fromexamination of 48 samples, results of anemia proportion in school age children at ?veorphanagesamounted to 29.16%. Most sampeles (> 80%) already got su? cientrecommendedRDA,except for vitamin Athatstill far below recommended RDA. From 48 of 28 samples (58,33%)havea habitof consuming milk and as many as 38 samples (79,16) consume tea.Theconclusion of this study is that school age children are vulnerable to iron de?ciency,anemia, andhavethe habitof consuming iron inhibitors.